Enhancing quinoline and phenol removal by adding Comamonas testosteroni bdq06 in treatment of an accidental dye wastewater. (November 2016) - Liu, Jing; Yu, Yang; Chang, Ying; Li, Baikun; Bian, Dejun; Yang, Wu; Huo, Hongliang; Huo, Mingxin; Zhu, Suiyi
Abstract: Accidentally released dye wastewater, which contained high concentrations of quinoline, phenol and other phenolics, was successfully treated by adding Comamonas testosteroni bdq06 and supplementing with domestic wastewater. Higher efficiency of 85.1% TOC removal was achieved by the bioaugmentation comparing to the control and no significant shock was observed from increasing the organic loadings. For the control, the removal of TOC was 11.1% less and the recovery of the shock was about 12 days. The addition of C. testosteroni bdq06 enhanced complete degradation of quinoline, phenol and other refractory compounds in the wastewater. DGGE result demonstrated that the inoculated C. testosteroni bdq06 adapted and proliferated in the process and predominated in quinoline degradation. Adding C. testosteroni bdq06 was shown to be an effective method for the treatment of wastewater containing quinoline, phenol and other refractory compounds.